Coexistence of Woolly Hair and Monilethrix: A Cases Study - Musbah, Fauzia khalifa (Al-Mukhtar Journal of Sciences, 2021)
Both Monilethrix and Woolly hair are considered as a rare autosomal dominant disorder with variable penetrance. Woolly hair exhibits short, kinked hair, which may also comprise the hair over the other places of the body. While Monilethrix is characterized by fragile hair that causing in patchy dystrophic alopecia. Here, we report a case of two sisters with an abnormality of scalp hair characterized by shorter, dry, finer light brown, kinky with a tangled appearance throughout the scalp. Trichoscopic and microscopic findings achieved the diagnosis. A therapeutic application with topical minoxidil was performed.